Innovation in Fish Cake Production: Proportions of Dory fish (Zeus faber) and Cassava (Manihot esculenta) with the Addition of Water Clover (Marsilea crenata) - Alfian Wahyu Pebriansah; Lilis Sulandari; Niken Purwidiani; Ita Fatkhur Romadhoni (JURNAL ILMIAH NUSANTARA, 2026)
Background: This research is intended to increase national fish consumption, which is currently uneven, through the production of fish cakes using Dory fish and cassava as the main ingredients. This innovation aims to minimize production costs while enhancing the nutritional content of the fish cakes. Purposes: This research aims to develop an innovative fish cake product by utilizing John Dory (Zeus faber), cassava (Manihot esculenta), and the addition of water clover leaves (Marsilea crenata) as alternative ingredients that are both nutritious and economical. Methods: The research method employed is a true experimental design featuring three treatment proportions of John Dory and cassava—80%:20%, 70%:30%, and 60%:40%—with the addition of 50 grams of water clover to each treatment. Result: There were significant differences across all organoleptic aspects for each treatment. The best results were achieved with the proportion of 80% John Dory and 20% cassava, which received the highest scores in appearance (19.4), color (20.76), texture (22), aroma (21.2), and flavor (20.44). Conclusion: The addition of cassava and water clover in the proper proportions can produce an innovative fish cake with good organoleptic quality and the potential to increase fish consumption among the public. Keywords: fish cake, ikan dori, singkong, semanggi, uji organoleptik